Are Sub‐Saharan epileptic people less photosensitive? A Senegalese study of photoparoxysmal response in a reference epilepsy centre*. Issue 5 (24th November 2020) - Magnerou, Annick Melanie; Toffa, Dènahin Hinnoutondji; Sow, Adjaratou Dieynabou; Basse, Anna; Seck, Lala Bouna; Ndiaye, Moustapha; Diop, Amadou Gallo
Abstract: Aims The photoparoxysmal response (PPR) is defined as the occurrence of generalized spike, spike‐wave or polyspike‐wave discharges consistently elicited by intermittent photic stimulation (IPS). PPR is not well studied in Sub‐Saharan African people. We prospectively studied the epidemiological, clinical, and EEG characteristics of PPR among consecutive patients recorded at the clinical neurophysiology unit of Fann University Hospital (Dakar, Senegal). Methods Among 6, 808 EEG recordings including 3, 065 pathological EEGs, we collected 56 EEGs with PPR (0.8% of all recorded EEGs and 1.8% of anormal EEGs), from 31 women and 25 men (sex ratio: 0.8). The mean age was 13.3 years (range: 8 months to 59 years). Results The peak of photosensitivity was found in the range of 6 to 10 years. Of the PPR cases, 12 had clinical manifestations during IPS. Generalized epilepsy was diagnosed in 23 (41%) patients and 18 (32%) had focal epilepsies. The most epileptogenic stimulation frequencies were between 12 and 24 Hz (range: 1‐28 Hz). PPR were mainly triggered during eye closure (64%), and 41 patients (73% of PPR cases) were classified as Type 4 (Waltz classification). Conclusions Our results confirm lower rates of photosensitivity in African Sub‐Saharan people compared with others. Although the current data do not support a role of short‐term ambient light levels, subject to consistent data from larger cohorts, it may be interesting to study the probable epigenetic‐mediated protective role of sunshine against photosensitivity.